MAINTENANCE SYMPHYSODONDISCUS WITH DIFFERENT FEED ON RECIRCULATION SYSTEMS - Marginata, Evodias; Putra, Iskandar; ', Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from December2014 until January 2015, for45 days in Aquaculture Technology Laboratory of Fisheries Faculty and MarineSciences, University of Riau. This study aimed to determine the effect of type offeeding is best to fish growth and survival of discus in the recirculation system.The method used in this study was a laboratoryscale experimental methods withdesign Completely Randomized Design (CRD) with three treatments were giventreatment level is P1 = Tubifex, sp, Moina, sp = P2, and P3 = Artificial Pellets.The best result was treatment P3treatment using feed artificial pellet absoluteweight of 4.3 g and absolute length of 1.3 cm. Survival and body color discus bestat using P3feed artificial pellet.Keyword : Symphysodondiscus, feed,recirculation